Dynamical Analysis of a Mathematical Model of COVID-19 Spreading on Networks - Li, Wang; Fu, Xinjie; Sun, Yongzheng; Liu, Maoxing (Frontiers in Physics, 2021)
In this article, an SEAIRS model of COVID-19 epidemic on networks is established and analyzed. Following the method of the next-generation matrix, we derive the basic reproduction number R0, and it shows that the asymptomatic infector plays an important role in disease spreading. We analytically show that the disease-free equilibrium E0 is asymptotically stable if R0≤1; moreover, the effects of various quarantine strategies are investigated and compared by numerical simulations. The results obtained are informative for us to further understand the asymptomatic infector in COVID-19 propagation and get some effective strategies to control the disease.